Global burden of 87 risk factors in 204 countries and territories, 1990–2019: a systematic analysis for the Global Burden of Disease Study 2019 - GBD 2019 Risk Factors Collaborators (Elsevier, 2022)
This article was published in The Lancet [ © 2020 The Author(s). Published by Elsevier Ltd. This is an Open Access Article under the CC BY 4.0 license..] and the definite version is available at: https://doi.org/10.1016/S0140-6736(20)30752-2. The Journal's website is at: https://reader.elsevier.com/reader/sd/pii/S0140673620307522?token=E2EB1CA6EF13B50B22B60D188E461581823C4F3CBFD50F3CAEB584555F3E1772A4944895BD9B142AA283FB2F37C0B1B5&originRegion=eu-west-1&originCreation=20220523052317